The effect of short online pedagogical training on university teachers’ interpretations of teaching–learning situations - Henna Vilppu; Ilona Södervik; Liisa Postareff; Mari Murtonen (Springer Netherlands, 2022)
The aim of the study was to explore whether short online pedagogy courses can have an effect on university teachers’ interpretations of teaching–learning situations. Before and after participating in a short online pedagogical training programme, a total of 66 participants wrote their interpretations of two short video clips, which depicted a content-focused teacher and a learning-focused teacher, respectively. The training was successful in changing participants’ interpretations from a knowledge-transmission view to a learning-facilitation view of teaching. This result indicates that even short online training programmes have the potential to affect participants’ interpretations of teaching–learning situations, especially when participants are not very experienced in teaching. Therefore, pedagogical training should be offered already at the early stages of teaching careers.